PENGARUH MANAJEMEN KELAS DAN ETOS KERJA GURU TERHADAP EFEKTIVITAS PROSES BELAJAR MENGAJAR DI SMP KELAS VIII - Dita Ayu Novitasari; Fakhruddin; Panca Dewi Purwati; Sri Sumartiningsih; Universitas Negeri Semarang (STKIP Subang, 2024)
The decline in the effectiveness of the learning process in schools is caused by suboptimal classroom management and a less than optimal work ethic among teachers. The purpose of this study is to examine the effects of classroom management and teacher work ethic on the effectiveness of the teaching and learning process in eighth-grade junior high schools. This research employs a quantitative method with a descriptive approach, involving a population of 160 eighth-grade students at SMPN 2 Pabelan, divided into 5 learning groups, each containing 32 students. The sample was taken using purposive sampling techniques and Slovin's formula, resulting in a sample size of 128. Data were collected through questionnaires, and the analysis was implemented using multiple linear regression tests. The findings of the study indicate that classroom management and teacher work ethic have a significant impact on the effectiveness of the learning process, both individually and collectively.